Impacts of Temenggor Dam on the socio-economi conditions of orang asli of the Temenggor Lake area - S.M. Rezaul Karim; Mansor M. (2013)
A socio-economic survey was done in two villages, Kampong Bersia and Kampong Chuweh, Tasik Temenggor Lake, Perak, Malaysia during 01 May to 30 June 2010 to study the impacts of newly constructed dams on the Temenggor Lake on the socio-economic conditions of Orang asli living in the lake areas. Tasik Temenggor Lake is the second largest lake in the Peninsular Malaysia, which is a source of income of a big number of peoples through fish culture, education, training, recreation and others. Orang asli have been living in different islands within this big lake. A structured questionnaire was used to collect the data. A translator was used to translate bahasa Melayu to English. Collected data were analysed properly to generate the information. It was noticed that a remarkable negative impacts of dams on the socio-economic conditions of Orang asli were occurred. Stopping of spontaneous water flow as the effects of dams and the addition of sewerage water from different cities to the lake, the quality of water is impaired; species diversity and availability of fishes were reduced by 40%. The income of the Orang asli has been reduced to RM 400/month only. Attention of Orang asli has been diverted to illegal logging and hill agriculture. Illegal logging near the lake shore made sedimentation in the lake. Many fishes were died due to reduced water quality.